PERLINDUNGAN HUKUM TERHADAP HAK ATAS MEREK PADA PERUSAHAAN STARTUP DIGITAL YANG TIDAK MENDAFTARKAN MEREK DAGANG DI BANDUNG - Rizka Aprilia; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Registering a trademark is very important for entrepreneurs today. Trademarks include company names and logos, names and symbols of certain products from companies and company slogans. As you know, there are still many digital startups that have not registered their trademarks. In fact, the existence of IPR certificates is considered quite important to protect its business from piracy, imitation or other problems and when there are investors who are interested in working together. Where IPR in general or trademark specifically is the foundation of a digital startup company Regulations related to brands are regulated in Law Number 20 Year 2016 Regarding Trademarks and Geographical Indications. Even though the various phenomena present show the enormous potential of the creative economy, it turns out that there are not many startups who consider IC to be an important issue, which is the problem at hand.The purpose of this thesis is; First, legal protection of trademark rights at digital startup companies that do not register trademarks in Bandung. Second, barriers faced against trademark rights in digital startup companies that do not register trademarks, Third, solutions or efforts made by the Creative Economy Agency. This type of research is sociological juridical research, which is research that emphasizes the legal aspects of the subject matter to be discussed, related to the reality in the field.From the results of research and discussion, there are three main things that can be concluded, First, legal protection of the rights to trademarks in digital startup companies that do not register trademarks can be done, based on the provisions of Article 21 paragraphs (1) letters b and c which contain the application refusal registration and be strengthened by Article 76 regarding the claim for cancellation of the mark. Second, the obstacles faced by digital startups in trademark registration are the lack of knowledge and understanding of the importance of IP protection, the lack of understanding of IP by the organizers and the Time Management related to trademark registration. Third, solutions or efforts made by Bekraf to increase awareness of digital startup companies on trademark registration by holding programs such as Facilitation of IPR registration, IPR protection seminars for ecraf products and IPR socialization etc.Keywords : Trademark, Startup Digital,Trademark Registrasion.